Temples and Mysteries in Romantic Infidel Writing - Priestman, Martin (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
AbstractNot all apparently religious imagery in Romantic Period writing is in fact religious. Temples—particularly when presided over by a priestess and linked with the ideas of reason or nature—often denote active hostility to Christianity if not to all religion. Examples from the Temple of Reason in revolutionary Paris to Shelley are considered, as well as references to Eleusinian and other Greek Mystery cults, seen as revealing hidden truths to an elite while concealing them from the masses. For Coleridge, these truths were quasi-Christian; for many others, they were materialistic and religiously subversive, but suppressed for political reasons. Hints of the latter position are briefly examined in Godwin, Richard Payne Knight, and Blake, as are some parallels in Freemasonry. Perhaps the fullest poetic use of temple and Mystery imagery is in The Temple of Nature (1803) by Erasmus Darwin, grandfather of Charles, whose evolutionary theory it anticipates. Despite a brief deistic identification of God as First Cause, its opening uses an exciting technique of imagistic montage to overthrow the story of Adam and Eve as a vulgar myth, to be replaced by an Eleusinian-style initiation of the few into the truths of the materialist self-sufficiency of nature. Its elaboration of these images makes it a crucial reference-point for their use in religiously unorthodox Romantic period literature.